2022
DOI: 10.3390/jcm11020330
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Compared to Trabecular Bone Score in Primary Hyperparathyroidism

Abstract: Individuals with primary hyperparathyroidism (PHPT) have reduced bone mineral density (BMD) according to dual X-ray absorptiometry at cortical sites, with relative sparing of trabecular BMD. However, fracture risk is increased at all sites. Trabecular bone score (TBS) may more accurately describe their bone quality and fracture risk. This study compared how BMD and TBS describe bone quality in PHPT. We conducted a retrospective cross-sectional study with a longitudinal component, of adults with PHPT, admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In one study of 106 men and women with acromegaly (mean age 56 y), despite lower TBS in vertebral fracture cases (1.18 vs. 1.202, p < 0.05), TBS was not associated with prevalent vertebral fractures in a multivariate model [ 134 ]. In the other nine studies, TBS was associated with prevalent vertebral fractures, independent of BMD [ 131 133 , 135 , 137 140 ] or enhanced fracture prediction when combined with BMD [ 136 ]. In four of these studies, however, BMD did not differ between fracture and non-fracture cases [ 131 , 133 , 135 , 139 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study of 106 men and women with acromegaly (mean age 56 y), despite lower TBS in vertebral fracture cases (1.18 vs. 1.202, p < 0.05), TBS was not associated with prevalent vertebral fractures in a multivariate model [ 134 ]. In the other nine studies, TBS was associated with prevalent vertebral fractures, independent of BMD [ 131 133 , 135 , 137 140 ] or enhanced fracture prediction when combined with BMD [ 136 ]. In four of these studies, however, BMD did not differ between fracture and non-fracture cases [ 131 , 133 , 135 , 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies examined TBS and hyperparathyroidism or hypoparathyroidism; conditions which are known to lead to alterations to trabecular bone microarchitecture [ 141 , 142 ]. In studies of patients with hyperparathyroidism or hypoparathyroidism, TBS was significantly lower in fracture compared to non-fracture cases [ 132 , 135 , 137 , 139 , 140 ]. In studies that examined the skeletal profiles of fracture cases, the prevalence of degraded TBS (35 to 57%) was greater than densitometric osteopenia or osteoporosis (11 to 21%) [ 137 , 139 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, newer studies based on microfinite element models obtained from high-resolution peripheral quantitative computed tomography (HRpQCT) images showed that in PHPT, there is a significant stiffness decrease in cortical and trabecular scores, 16 , 17 along with a decreased trabecular number, volumetric BMD, and connectivity. 18 - 20 …”
Section: Introductionmentioning
confidence: 99%